Environmental Licensing Challenges of Xingu Rio Transmission System Route Definition - Cardoso Junior, Ricardo Abranches Felix; Hoffmann, Alessandra Schwertner (Ciência e Natura, 2018)
Based on the Brazilian electric sector planning, by 2026 the transmission grid will be increased by 64 thousand km, so that the analysis of how to incorporate the environmental criteria in the discussions of route optimization are important for the decision-making of the various actors (government, environmental agencies and entrepreneurs). Therefore, this article aims to identify the challenges of the incorporation of the socio-environmental criteria for the route optimization as well as the deadlines and costs of the Xingu-Rio Transmission System known to be the largest transmission system in Brazil.